1988
DOI: 10.1111/j.1532-950x.1988.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Steady State and Transient Thermography Techniques Using a Healing Tendon Model

Abstract: Steady state and transient thermal techniques were used to define the thermal signatures of surgically sectioned and sham-operated common calcanean tendons in four dogs. All limbs were imaged from the lateral side using an Inframetrics 525 system at - 1, 2, 4, 6, and 8 weeks after surgery. Individual video frames were used to compute absolute surface temperatures and rewarm curves for five predetermined 1 cm2 skin areas. Angiography was performed at each observation period to correlate changes in vascular morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…Similar changes have been observed in equine inflammatory joint disease 29,31 . In experimentally induced calcanean tendon tears in dogs, this same asymmetry and increase in color map and temperature over the injured region were noted 37 …”
Section: Thermographysupporting
confidence: 76%
See 1 more Smart Citation
“…Similar changes have been observed in equine inflammatory joint disease 29,31 . In experimentally induced calcanean tendon tears in dogs, this same asymmetry and increase in color map and temperature over the injured region were noted 37 …”
Section: Thermographysupporting
confidence: 76%
“…Thermography in dogs has been limited to research applications but is being used clinically in our hospital. 26,33–37 …”
Section: Thermographymentioning
confidence: 99%
“…In contrast to humans and horses, little is known about thermographic imaging of the canine stifle. Use of thermography in small animal medicine has been largely limited to research, with no clinical applications being reported 54–59 . Because of the noninvasive nature of this imaging modality without need for anesthesia or use of radiation in image generation, thermography may be a useful diagnostic screening technique for disorders of the canine stifle.…”
mentioning
confidence: 99%
“…Use of thermography in small animal medicine has been largely limited to research, with no clinical applications being reported. [54][55][56][57][58][59] Because of the noninvasive nature of this imaging modality without need for anesthesia or use of radiation in image generation, thermography may be a useful diagnostic screening technique for disorders of the canine stifle. Thus, our purpose was to compare thermal patterns and temperature gradients in the stifle region of clinically normal dogs, before and after hair clipping, with those of dogs with CCL-deficient stifles.…”
mentioning
confidence: 99%
“…Alterações térmicas nos tendões foram identificadas por termografia até duas semanas antes de alguns animais apresentarem sinais clínicos de tendinite (TURNER, 2001). A termografia pode detectar alterações vasculares num tendão de estrutura comprometida (STEIN et al, 1988). Um estudo que correlacionou termografia, histologia e microangiografia concluiu que as alterações degenerativas precedem os sinais clínicos quanto ao aparecimento da tendinite (STROMBERG, 1973).…”
Section: Etiopatogenia Da Tendiniteunclassified